(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Hybrid wars as a new generation of conflicts are largely discussed today. The purpose of this article is to analyze Gerasimov’s doctrine, by interpreting its main aspects. The analysis is based on original empirical research of his publications.